Remembering Rajiv - Aiyar, Mani Shankar (Calcutta : Rupa & Co., 1992)
Autobiographical reminiscences of the author about the former prime minister of India; previously published in various journals and newspapers.
Keywords: Prime ministers -- India -- Biography; India -- Politics and government -- 1977-